The Kansas-Sudan Missionary Movement in the Y.M.C.A., 1889-1891 - Hopkins, C. Howard (Church history, 1952)
Among the significantly great historical achievements of the American Young Men's Christian Associations has been the planting of Associations in foreign countries. Paralleling the notable missionary outburst of the late nineteenth century among the North American churches, this distinctive program of the YMCA was inaugurated in the last years of the 1880's with the sending of Association secretaries to Japan and to India.1 Nourished in the student Y.M.C.A.'s and particularly evangelized at the pioneer student conferences held under the auspices of Dwight L. Moody in Northfield, Massachusetts, beginning in 1886,2 the missionary fervor aroused significant interest in many Associations. By 1916 there were 157 North American secretaries in 55 foreign countries, 140 of them in Asia.